2018
DOI: 10.3389/fnana.2018.00035
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Mechanism of Age-Related Synaptic Dysfunction Based on the Impact of IGF-1 Receptor Signaling on Synaptic CaMKIIα Phosphorylation

Abstract: Insulin-like growth factor 1 receptor (IGF-1R) signaling regulates the activity and phosphorylation of downstream kinases linked to inflammation, neurodevelopment, aging and synaptic function. In addition to the control of Ca2+ currents, IGF-1R signaling modulates the activity of calcium-calmodulin-dependent kinase 2 alpha (CaMKIIα) and mitogen activated protein kinase (MAPK/ErK) through multiple signaling pathways. These proteins (CaMKIIα and MAPK) regulate Ca2+ movement and long-term potentiation (LTP). Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 90 publications
1
10
0
Order By: Relevance
“…This result is in line with previous observations, although in mouse lung cells exposed to cigarette smoke, where Egr-1 was able to regulate HO-1 ( Chen et al, 2010 ). Finally, our data showed that this signaling may be sustained by the phosphorylation of ERK1/2 in the old brain cortex, which has already been described to be more activated during aging and to be associated to synaptic dysfunction ( Ogundele et al, 2018 ). Furthermore, in smooth muscle cells Egr-1 was demonstrated to be activated via ERK1/2 under OS conditions ( Pagel and Deindl, 2012 ).…”
Section: Discussionsupporting
confidence: 68%
“…This result is in line with previous observations, although in mouse lung cells exposed to cigarette smoke, where Egr-1 was able to regulate HO-1 ( Chen et al, 2010 ). Finally, our data showed that this signaling may be sustained by the phosphorylation of ERK1/2 in the old brain cortex, which has already been described to be more activated during aging and to be associated to synaptic dysfunction ( Ogundele et al, 2018 ). Furthermore, in smooth muscle cells Egr-1 was demonstrated to be activated via ERK1/2 under OS conditions ( Pagel and Deindl, 2012 ).…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, Bhat et al, reported that a high-fat/high-cholesterol diet can promote cognitive decline and brain dysfunction [ 156 ]. High fat diet (HFD)-induced obesity altered the circulating IGF cascade and increased circulatory level of total IGF-1, IGF-2, free IGF-1, and IGFBP3 in rodent and clinical trials [ 157 , 158 ]. However, insulin/IGF signaling (IIS) may be critical in diet-induced AD-like pathology.…”
Section: Metabolic Syndrome and Neuropathologymentioning
confidence: 99%
“…There is a considerable increase in neural MAPK phosphorylation with aging along with a decrease in Calcium/Calmodulin-Dependent Protein Kinase IIa (CaMKIIa) levels. Changes in the phosphorylation of synaptic kinases (CaMKII and MAPK) involved in the regulation of long-term potentiation may be related to IGF-1/IGF-1R signalling [ 158 ]. IGF-1 was recently identified as belonging to a new class of ion channel modulators with rapid response (Fig.…”
Section: Metabolic Syndrome and Neuropathologymentioning
confidence: 99%
“…Insulin-like growth factor type 1 receptor (IGF1R) is an important cellular modulator with essential roles in the regulation of growth, development and metabolism, as well as in cellular processes like proliferation, survival, cell migration and differentiation; affecting nearly every organ system in the body [ 1 , 2 , 3 ]. Belonging to the family of transmembrane receptor tyrosine kinases (RTKs), where it is also included its highly homologous insulin receptor (IR), IGF1R is a transmembrane heterotetrameric glycoprotein consisting of two extracellular α subunits containing the IGF-binding site and two intracellular β subunits that exhibit tyrosine kinase activity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%